Removal of tenacious glumes enhances the seed germination and seedling vigour in eight Aegilops species for efficient conservation in genebank - SRINIVASAN, K; RADHAMANI, J; KALKANDE, T; TYAGI, R K (The Indian Journal of Agricultural Sciences, 2026)
Wild species, which are potentially valuable sources of resistance, play a very prominent role as donors of stress resistant genes in crop improvement programmes. Thus, their conservation in the form of seeds in the genebanks is of paramount importance for their availability in breeding programmes. High initial seed quality is one of the important prerequisites for long-term conservation in genebanks which is measured in terms of seed germination and vigour. Aegilops species exhibit inherent problems caused by erratic and staggered germination due to dormancy imposed by presence of tenacious glumes. Objective of this study was to evaluate the effects of removal of glume to assess the initial seed germination and seedling vigour of eight wild species of wheat before their long-term storage in genebank. Germination in seeds with glume was recorded as 20-70% and in seeds without glume was 72-100%. It is concluded that tenacious glumes contribute to the physical dormancy and removal of glumes increased the germination and seedling vigour in all eight species namely Ae. bicornis, Ae. geniculata, Ae. kotschyi, Ae. longissima, Ae. triuncialis, Ae. umbellulata, Ae. vavilovii, and Ae. ventricosa. We recommend that the genebank curators can follow this method to assess the initial seed viability, which is pre-requisite, for long-term conservation of valuable donor Aegilops species in genebank.